Impact of the Marine Transport System and Public Administration on the Environmental Protection - MANASBAY, Aigul; BEISENGALIYEV, Berik; TUREKULOVA, Assiya; KURMANKULOVA, Nurzhamal; TUREKULOVA, Dametken (Journal of Environmental Management and Tourism; Vol 12 No 3 (2021): JEMT Volume XII Issue 3(51) Summer 2021, 2021)
In connection with the development of the economy and the increasing scale of human economic activity, the transportation of various goods by sea (water) transport is increasing, which make up 60-67% of the world cargo turnover. At the same time, there is a negative impact on the environment, its pollution, the consequences of which affects both the current generation and may affect the future. Therefore, the impact of water transport on the environment is an urgent and pressing problem of today, but it is necessary to note the positive aspects of the development of the country's water transport, which has an impact on the creation of an additional export and transit route for the transportation of goods, the entry of Kazakhstani goods to world markets and the creation of additional jobs in this industry.